Guidance for Ophthalmologists and Ophthalmology Centers during the COVID-19 Pandemic - Rajavi, Zhale; Safi, Sare; Mohammadzadeh, Maryam (Journal of Ophthalmic and Vision Research, 2020)
This is a Letter to the Editor and does not have an abstract.